Protocol for the development of Polish clinical guidelines for the management of patients with systemic lupus erythematosus - Joanna Makowska; Brygida Kwiatkowska; Magdalena Krajewska-Włodarczyk; Bogdan Batko; Marcin Stajszczyk; Jerzy Świerkot; Zbigniew Żuber; Piotr Leszczyński; Agata Sebastian; Magdalena Władysiuk; Irena Walecka; Michał Chmielewski; et al. (Rheumatology)
Introduction Systemic lupus erythematosus (SLE) is a complex, chronic autoimmune disease that causes multi-organ inflammation and damage. Left untreated or inadequately managed, SLE can lead to severe organ dysfunction, disability, and reduced quality of life. In Poland, the absence of standardized, evidence-based clinical guidelines tailored to local resources and practices has created inconsistencies in SLE management. The purpose of these guidelines is to provide clear, evidence-based recommendations for the treatment and management of adult patients with SLE in the Polish healthcare system. These recommendations aim to align clinical practices with international standards, optimize treatment strategies, standardize patient care, and improve health outcomes while guiding healthcare policy.